EFFECTIVE PEDAGOGICAL APPROACHES AND STRATEGIES IN MODERN EDUCATION - Abidova Umida Rustamovna (TADQIQOTLAR, 2025)
Abstract: This study explores various pedagogical approaches and strategies that  contribute  to  effective  teaching  and  learning.  Drawing  on  contemporary educational theories and practices, the paper examines the implementation of learner-centered, constructivist, and inquiry-based methods. Findings suggest that adaptive and flexible pedagogical strategies significantly enhance student engagement and academic performance.